La marcia degli alfabeti. Indagine semiologica degli Slavs and Tatars - Davide Tolfo (Ocula)
Introducing the artistic practice of the collective Slavs and Tatars, this essay aims to analyze the ways in which visual communication and linguistic analysis are integrated in their works within a critical and experimental approach. Expanding on the categorization proposed by art historian David Joselit, it will examine how the collective privileges propositions, documents, and ready-mades as central forms of their operations. In conclusion, the proposed analyses will highlight the departure of Slavs and Tatars from a postmodern artistic approach.